2018
DOI: 10.4103/ijri.ijri_107_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the diagnostic efficacy of full field digital mammography with digital breast tomosynthesis using BIRADS score in a tertiary cancer care hospital

Abstract: Introduction:Breast cancer is one of the leading cancers in females worldwide, and its incidence has been rising at an exponential pace in the last 10 years even in India. Mammography has been the mainstay for detection of breast cancer over decades and has gradually advanced from screen film to full-field digital mammography. Recently, tomosynthesis has evolved as an advanced imaging investigation for early diagnosis of breast lesions in both diagnostic and screening settings.Aim of Study:To compare and evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
2
14
1
Order By: Relevance
“…Our results were comparable to prior studies done by Conant et al [11], Skaane et al [12], and Divya et al [13] who reported increased sensitivity, specificity, and increased cancer detection when DBT was used. Skaane et al found increase sensitivity from 54.1 to 70.5% and mild increase in specificity from 94 to 95% by using DBT compared to digital mammography [12].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results were comparable to prior studies done by Conant et al [11], Skaane et al [12], and Divya et al [13] who reported increased sensitivity, specificity, and increased cancer detection when DBT was used. Skaane et al found increase sensitivity from 54.1 to 70.5% and mild increase in specificity from 94 to 95% by using DBT compared to digital mammography [12].…”
Section: Discussionsupporting
confidence: 91%
“…Our results were comparable to a study performed by Divya et al [13], which conducted a comparison between DBT and FFDM according to the BIRADS scoring. With the addition of tomosynthesis to FFDM 53% of the cases changing their BIRADS scoring, BIRADS was upgraded in 14% and downgraded in 31% of cases and DBT did not change the BIRADS scoring in 47% of cases but its addition increased the diagnostic confidence.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Singla et al, 23 found that in most cases (47) DBT did not change BIRADS scoring but its addition increased the diagnostic confidence. Almost similar results were reported by our study where BIRADS was upgraded in only 3 cases and downgraded in only one case with the addition of DBT to FFDM.…”
Section: Discussionmentioning
confidence: 99%